2013
DOI: 10.1021/ie4000932
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of the Extractive Distillation for the Production of Fuel-Grade Ethanol

Abstract: The extractive distillation of ethanol using glycerol as the entrainer was studied to determine its optimal control profiles when the azeotropic feed was subjected to composition disturbances. The process was modeled by a differential-algebraic equation (DAE) system that represents the dynamics of the equilibrium stages in the extraction column. The model equations were solved by discretizing the time domain using orthogonal collocation on finite elements. Initially, the effects of feed disturbances on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…The non-linear dynamic optimisation problem that needs to be solved is very challenging (computationally speaking) and thus simplified models as well as efficient solving strategies are required. Ramos et al (2013Ramos et al ( , 2014 studied the optimal control profiles of the extractive dehydration of ethanol using glycerol as entrainer when the azeotropic feed was subject to step-wise and sinusoidal disturbances. The goal was to help tailoring nonlinear model-predictive control strategy implemented in a real production facility.…”
Section: Control Of Batch Extractive Distillation Luyben Andmentioning
confidence: 99%
“…The non-linear dynamic optimisation problem that needs to be solved is very challenging (computationally speaking) and thus simplified models as well as efficient solving strategies are required. Ramos et al (2013Ramos et al ( , 2014 studied the optimal control profiles of the extractive dehydration of ethanol using glycerol as entrainer when the azeotropic feed was subject to step-wise and sinusoidal disturbances. The goal was to help tailoring nonlinear model-predictive control strategy implemented in a real production facility.…”
Section: Control Of Batch Extractive Distillation Luyben Andmentioning
confidence: 99%
“…Control of the fermentation reactor for bioethanol production has been pursued within the framework of optimal control [166] and MPC [167][168][169][170]. Similarly, control of the separation system has been targeted using PI control [171,172] and optimal control [173]. In the context of bio-diesel production, most of the control studies have focused on the control of the transesterification reactor which is the heart of the bio-diesel production process.…”
Section: Renewable Fuelsmentioning
confidence: 99%
“…17 There are many alternatives to overcome the azeotropic point, such as vacuum distillation, azeotropic distillation, and extractive distillation. Different possibilities of extractive distillation can be considered according to the entrainer used, and it has been reported that glycerol has a good performance for this system.…”
Section: Case Studymentioning
confidence: 99%